Mergers and competition policy : report of the Committee of Experts on Restrictive Business Practices - Organisation for Economic Co-operation and Development (Paris : Organization for Economic Co-operation and Development, 1974)
The report pays particular attention to the economic aspects of mergers and their implications for government policy
Includes bibliographical references.
obn25/01/2019
Loans
Keywords: Consolidation and merger of corporations; Antitrust law; International business enterprises